2018
DOI: 10.1093/jxb/ery194
|View full text |Cite
|
Sign up to set email alerts
|

Na+ extrusion from the cytosol and tissue-specific Na+ sequestration in roots confer differential salt stress tolerance between durum and bread wheat

Abstract: Stronger Na+ extrusion and vacuolar sequestration are essential to confer better salt tolerance in bread wheat than in durum wheat. Removal of the root meristems increased salt sensitivity in wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 97 publications
4
56
1
Order By: Relevance
“…Salt overly sensitive (SOS1), which encodes a PM Na + /H + antiporter, is preferentially expressed in the root tip rather than in the mature zone in Arabidopsis (Shi, Quintero, Pardo, & Zhu, ). Outside the meristem zone, wheat ( Triticum aestivum ) exhibits hypersensitivity to salt stress with significant Na + accumulation in the cytosol but not in the vacuole, which confirms that the root apex has a stronger Na + signal (Wu et al, ). Taken together, these results confirm that the root apex exhibits a strong ion flux in various species and is associated with much of the observed electrophysiology (see review by McLamore & Porterfield, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Salt overly sensitive (SOS1), which encodes a PM Na + /H + antiporter, is preferentially expressed in the root tip rather than in the mature zone in Arabidopsis (Shi, Quintero, Pardo, & Zhu, ). Outside the meristem zone, wheat ( Triticum aestivum ) exhibits hypersensitivity to salt stress with significant Na + accumulation in the cytosol but not in the vacuole, which confirms that the root apex has a stronger Na + signal (Wu et al, ). Taken together, these results confirm that the root apex exhibits a strong ion flux in various species and is associated with much of the observed electrophysiology (see review by McLamore & Porterfield, ).…”
Section: Discussionmentioning
confidence: 86%
“…Root K + and Na + levels are recognized as a key determinant of plant salt tolerance (Chen, Pottosin, et al, ; Chen, Zhou, et al, ; Lang et al, ; Shabala, ; Sun, Chen, et al, ; Sun, Dai, et al, ; Tester & Davenport, ; Wu et al, ). In the present study, we found that A. nanus roots under a combination of herbivore and salt stress had a higher K + content, a lower Na + content, and a higher K + /Na + ratio than plants subjected to salt stress alone (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that the root phenotype is altered in response to soil salinity (Shelden et al, 2013). Moreover, the ability for higher Na + extrusion in the root elongation zone and better vacuolar Na + sequestration in the mature root zone was found to be essential for salinity tolerance in bread wheat genotypes (Wu et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study has investigated salinity effects on root development at specific phytomer positions in hydroponic culture to provide a novel understanding of salinity damage in wheat roots (Robin et al, 2016). It was shown that salt stress sensor is located in the root meristem, and meristem signaling to the shoot is essential in enabling vacuolar Na + sequestration ability in leaf mesophyll cells (Wu et al, 2018). Recently, quatitative trait loci (QTLs) and markers linked with various micronutrient concentrations and salt tolerance have been identified at seedling stage in wheat (Hussain et al, 2017).…”
mentioning
confidence: 99%
“…The results regarding Na + and Cl - ions accumulation are rather interesting. High levels of Na + and Cl - ions were detected in roots of treated plants suggesting that the roots may act as potential sink for excessive Na + and Cl - ions deposition, inhibiting their translocation to shoot and alleviate the negative effects on actively dividing and photosynthesizing cells (Baetz et al, 2016; Peng et al, 2016; Rahneshan et al, 2018; Wu et al, 2018). Intriguingly, Ca 2+ levels were also increased with increasing Na + levels in both leaves and roots of salt treated plants, which suggest that might possible trigger of vaculoar Ca 2+ reserves to ameliorate the Na + toxicity (Saleh Plieth, 2013).…”
Section: Discussionmentioning
confidence: 99%